Computer concepts basic - Wells, Dolores; Ambrose, Ann Peele (Sinagpore, 2007)
Computer Concepts BASICS, Third Edition, is a brief introduction to computers. This text covers computer hardware, software, application skills, keyboarding skills, the Internet and Internet searching, Web page creation, networking, careers, and computer ethics. It can be used in any class on business applications, technology, or computer applications. This textbook, along with the Instructor's Resource CD-ROM and Activities Workbook, is all that is needed for a brief course on computer concepts and the Internet and can be used for 35 or more hours of instruc-tion. After completing these materials, the student should have an understanding of the basics of computers, how technology is changing the world in which we live, and the importance of the Internet
Keywords: Computers; Internet; Operating Systems